GENETIC AND PHENOTYPIC CORRELATION BETWEEN SOMATIC CELL COUNT AND MILK YIELD IN SAUDI DAIRY GOATS USING RANDOM REGRESSION ANIMAL MODEL - A. A. Amin (Journal of Animal and Plant Sciences, 2017)
The objective of the present study was to explain the genetic and phenotypic relationship between  test-day somatic cell count and score (SCC& SCS), with daily milk yield in Gabali and Aradi Saudi goat using the random regression animal model.  The total number of production records included in the present study was 2021 dairy records. 942 dairy records for Aradi goats and 1079 dairy records for Gabli Goats. All available data were collected from Station of training and agriculture-veterinary research, King Faisal University. Polynomial random regression of the third order seemed adequate to explain variation in somatic cell count and test-day milk yield. Somatic cell count (SCC) was examined each 15-days using digital instrument DCC. The overall mean of daily production was 886+41 ml for Aradi goat and 738+36 ml for Gabli goat. Overall mean of somatic cell count for Aradi goats was 983x103 cell\ml milk and for Gabli goats was 1127x103 cell\ml milk. Lowest somatic cell count (258x103 cell\ml milk) obtained during early stage of the 1st lactation.  While the highest somatic cell count, (2541x103cell\ml milk) obtained during the end of the 4th lactation.  The 3rd parity showed the highest daily milk production (873 ml) and the 4th parity showed the highest somatic cell count (1436x103 cell\ ml milk). Additive, Phenotypic and permanent environmental correlations were estimated using random regression animal model.  Additive genetic correlation between TDM and both of SCC and SCS were negative and ranged from -0.27 to -0.39 and -0.19 to -0.21, respectively. Estimates of additive genetic correlations between of somatic cell score decreased with increasing the interval between test-days. More details on estimates of different genetic parameters, estimates of permanent environmental and additive genetic correlations for all traits were tabulated.
Keywords: Correlation – milk - Somatic cell count – udder –goats